Teaching an Invisible Subject: How are we Educating Faculty about Copyright? - Zerkee, Jennifer (Journal of Copyright in Education & Librarianship, 2018)
Copyright can be an invisible issue for instructors because infringement or improper use of copyright-protected material will not impede teaching. Copyright law is nuanced and open to interpretation; it is not always clear whether a particular action is compliant or not. This poster will share the results of the presenter’s Canada-wide survey of university copyright administrators, exploring institutions’ provision of copyright education to instructors. The presenter found more questions rather than answers as a result of the survey. Most respondents do no assessment of their copyright instruction, and instead are comfortable relying on experience, questions from faculty, and anecdotal evidence to form an impression of instructors’ familiarity with copyright rules. Is informal appraisal adequate for ensuring that libraries and copyright offices are fulfilling their responsibility to encourage and enable the confident and lawful use of copyright-protected material? What other evidence could be gathered to inform copyright administrators’ efforts? This poster will encourage participants to think about copyright education at their institutions, will share the results of the survey, including approaches being taken by universities across Canada, and will share Simon Fraser University's approaches to instructor education